(3OhQ GdaSN GdGJaGbi ai GfgGA GdYbhO (B/ s - (3YeQ Ydi SYjO eMeO edjM GdTGeSi s; (3YHOGdQTjO eCehf TOjO s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2009)
(3ehVhY gPg GdQSGdI gh (B"(3OhQ GdaSN GdGJaGbi ai GfgGA GdYbhO(B" (3hbO JfGhdfG gPG ai aUd JegjOi(B: (3NUU dHjGf GdaSN hJWhQg GdJGQjNi ai GdYUhQ GdbOjeI(B: (3ceG bSefG GdHMK Gdi HGHjf GdGhd JYQVfG ajg dWHjYI GdaSN hJejjRg Yf ZjQg ef UhQ GdGfMdGd GdGNQi hbSe Gdi KdGKI aUhd(B: (3GdGhd JfGhdfG ajg GdebUhO HGdaSN hJMOjO eGgjJg hWHjYJg hGdaUd GdKGfi JfGhdfG ajg JejjR GdaSN Yf ZjQg ef UhQ GfMdGd GdYbhO GdGJaGbjI(B: (3hGdaUd GdKGdK JfGhdfG ajg GdYdGbI Hjf GdaSN GdGJaGbi hGdbGfhfi hGdbVGFi hGdJWHjbGJ GdbVGFjI dgs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdeOfi, (B2009s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI(B: (3UaMI (B441-458s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdeOfjs; (3GdaSN GdGJaGbis; (3GdaSN hJWhQg s; (3GfgGA GdYbhO s; (3GdCKQ GdQLYi ddJaGSNs; (3fXQjI GdTQW GdaGSNs; (3GdGfaSGN h hba GdYbOs; (3GfMdGd GdYbOs; (3YOe faGP GdJUQaGJs; (3GdHWdGfs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdeOfjs